Enacting Safety and Omitting Gender: Australian Human Rights Scrutiny Processes Concerning Alcohol and Other Drug Laws. (September 2022) - Seear, Kate; Mulcahy, Sean
Global momentum for drug law reform is building. But how might such reform be achieved? Many argue that human rights offer a possible normative framework for guiding such reform. There has been very little research on whether human rights processes can actually achieve such aims, however. This paper responds to this knowledge gap. It explores how one human rights mechanism—the "parliamentary rights scrutiny process"—deals with alcohol and other drugs. We consider how four Australian parliaments scrutinized proposed new laws that would deal with alcohol and other drugs for their human rights "compatibility." We find that laws that would limit the rights of people who use alcohol and other drugs were routinely seen as justifiable on the basis that alcohol and other drugs were inherently "unsafe." Crucially, safety was conceptualized in a gender-neutral way, without regard to the potential role of gender, including specific masculinities, in the production of phenomena such as family violence and sexual violence and other public safety problems. Instead, such problems were regularly constituted as consequences, simply, of alcohol or other drug consumption. In making this argument, we build on the pioneering work of David Moore and colleagues (e.g., 2020). Their work asks important questions about how the causes of violence are constituted across different settings, including research and policy. Drawing on ideas from scholars such as Carol Bacchi and John Law, they identify "gendering practices" and "collateral realities" in research and policy on violence, in which the role of men and masculinities are routinely obscured, displaced or rendered invisible. We find similar problems underway within human rights law. In highlighting these gendering practices and collateral realities, we aim to draw attention to the limitations of some human rights processes and the need for more work in this area.